IN VITRO EVALUATION OF THE ANTHELMINTIC ACTIVITY OF RHIZOME EXTRACTS OF CURCUMA LONGA (LINN.) - Pandey, Jyoti; Mishra, Suman; Jaiswal, Kamal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current study was carried out to evaluate the anthelmintic activity of the rhizome extract of Curcuma longa as an alternative source of effective remedies for nematodiasis. Methods: The anthelmintic activity of the C. longa was assessed in vitro against Haemonchus spp., a gastrointestinal (abomasum) parasite of goats. Different concentrations of the extracts (1 mg/mL, 2.5 mg/mL, 5 mg/mL, and 10 mg/mL) in phosphate-buffered saline (PBS) were tested, and the results expressed in terms of time of paralysis (minute) and time of death (minute) of the worms. Albendazole (1 mg/mL) was used as a reference (positive control) and PBS as a control group (negative control). Results: The qualitative phytochemical analysis of the methanolic extract (ME) of the plant disclosed the presence of alkaloids, glycosides, terpenoids, flavonoids, tannins, saponins, phenol, anthraquinone, and carbohydrates; whereas, the aqueous extract (AE) showed the presence of alkaloids, carbohydrate, flavonoids, and saponins. Both ME and AE of the C. longa (rhizome) expressed significant efficacy (pâ‰¤0.05) in causing paralysis as well as the death of the worms within 12 h of exposure at all tested concentrations, as compared to the negative control. The rhizome extracts of C. longa showed dose-dependent efficacy in causing paralysis of the worm motility and the final progression to death. The results showed that the ME at 10 mg/mL was significantly more potent (pâ‰¤0.05) over the AE. Conclusions: This study concluded that the rhizome extract of C. longa exhibited potent anthelmintic efficacy against the nematode parasite, Haemonchus spp.